The Application of Intelligent Architectural Design in Energy Saving and Sustainable Development - Wang, Qiang (Transactions on Social Science, Education and Humanities Research, 2024)
In today’s context, energy conservation, emissions reduction, and sustainable development are highly prioritized, and the architectural industry must recognize the value of intelligent buildings to maintain stable growth amidst fierce competition. Intelligent design not only enhances the energy efficiency of buildings, achieving energy savings and emissions reductions, but also significantly improves their safety and convenience, providing a more comfortable living environment for residents. Moreover, it is a key force driving technological innovation in the architecture industry, leading it towards more efficient, environmentally friendly, and sustainable development. In terms of application principles, intelligent architectural design emphasizes coordination, integrity, and flexibility. It requires considering the harmonious unity between architecture and the environment, ecosystems, and human needs during the design process, treating the building as an integrated system, and focusing on the flexibility and adjustability of the design to accommodate potential future changes. In specific applications, intelligent designs for natural lighting, ventilation, and electrical systems are important manifestations of intelligent architectural design. These applications, through intelligent control systems and devices, achieve efficient management and adjustment of the building environment, thereby enhancing the building’s energy efficiency and contributing to sustainable development.